Distinct recirculation potential of CD69+CD103− and CD103+ thymic memory CD8+ T cells. Issue 10 (2nd August 2016) - Park, Simone L; Mackay, Laura K; Gebhardt, Thomas
Abstract : Tissue‐resident memory T (TRM ) cells occupy peripheral and lymphoid tissues where they confer protection against local infection. While epithelial CD8 + TRM cells coexpress CD69 and CD103, CD103 − memory cells have been described in various organs and are often presumed non‐recirculating based on their expression of CD69. We found that both CD69 + CD103 + and CD69 + CD103 − memory cells populated the thymus upon transfer of CD8 + effector T cells into uninfected recipients. Transcriptionally and phenotypically, CD103 + thymic cells resembled non‐lymphoid TRM cells, whereas CD69 + CD103 − cells displayed a profile that was more closely related to recirculating cells. Although CD69 was required for optimal CD103 + TRM formation, its expression alone did not identify permanently resident cells, as CD69 + CD103 − cells disappeared from the thymus following antibody‐mediated depletion of recirculating cells. Our findings highlight a distinct migration potential of phenotypically divergent thymic CD8 + memory T cells and emphasise the inadequacy of CD69 as a marker of tissue residency.